(untitled) (JIKE : Jurnal Ilmu Komunikasi Efek, 2021)
Sexual violence that occurs with children is a disgraceful act that harms both parties, especially children. These cases have an emotional and physical impact on the victims. These are a concern for many elements of society and the Independent Volunteer Network Foundation (JaRI Foundation). The purpose of this study is to describe the application of interpersonal communication in assist psychological services in managing child sexual abuse at the JaRI Foundation and to explain the results of interpersonal communication to victims of child sexual violence at the JaRI Foundation. The researcher used a qualitative descriptive approach with the Five Attitudes of Interpersonal Communication, based on DeVito, to achieve the research objectives. To get the result of the research, several informants about experiences and perspectives of Psychologists, Victims of Child Sexual Violence, Parents, and Lecturers of Communication Studies. This study indicates ways applied in each of the five interpersonal communication attitudes: openness, empathy, supportiveness, positiveness, and equality. Then from these five attitudes, there is a result of interpersonal communication applied in counseling activities at the JaRI Foundation, namely a positive change in behavior after counseling at the JaRI Foundation and a change in emotional one of which is the emergence of a feeling of relief after counseling with a JaRI Foundation Psychologist. From the results of this study, it is stated that the interpersonal communication that is applied is quite good.